Characterization and genetic diversity of Rigidoporus microporus associated with white root rot disease in rubber tree (Hevea brasiliensis müll.arg.) - Andrew, Bernice (2020)
White root rot (WRR) disease caused by Rigidoporus microporus is a major disease affecting tropical rubber tree (Hevea brasiliensis) and some agricultural crops throughout the world. WRR disease causes major financial losses to growers as there is no effective method to control the disease in the field. There is limited information on the genetic variation of R. microporus, associated with WRR disease in Malaysia. In view of this, the objectives of this study were to characterize R. microporus isolates from rubber tree collected from different regions in Malaysia using morphological and molecular characteristics and to determine genetic diversity of R. microporus in Malaysia using somatic incompatibility (SI) test and inter-simple sequence repeat (ISSR). During July 2017 to May 2018, a total of 27 samples showing WRR symptoms such as presence of basidiocarps and rhizomorphs in five states of Malaysia including Kedah (Baling), Kelantan (FELCRA Machang and Smallholder in Machang), Perak (Ipoh) and Selangor (Sungai Buloh and UPM Serdang), Sarawak (Bintulu) were obtained. In the field observation, all sampling areas were infected by the root rot disease. Findings revealed that field disease incidence was in the range of 5-40% based on random sampling. The areas with the highest disease incident (30-40%) were RRIM Research Station Similajau, Sarawak (Nursery area), Kelantan (Smallholder in Machang), RRIM Research Station Sungai Buloh, Selangor (Germplasm) and Universiti Putra Malaysia, Serdang (Germplasm). This data indicated that the disease was prevalent on mature tree, but the disease was also detected on young tree (2 years old) with low disease incidence. Based on cultural morphology data, all the diseased samples collected were R. microporus. The isolates were pure white and displayed fluffy mycelial growth when cultured on Malt Extract Agar (MEA) medium. Majority of the isolates grew fast and within 7 - 8 days on MEA plates at 30°C. For molecular identification, BLASTn analysis showed 98 to 100% identical to existing reference sequences in the GenBank database. Phylogenetic analysis based on ITS, β-tubulin and tef1 gene and the concatenation of the three genes confirmed that all 27 R. microporus isolates in this study were clustered into a clade with the reference sequences from Southeast Asia such as Malaysia, Thailand and Indonesia supported with bootstrap values of 95%, 92%, 98% and 99%, respectively. There was also no geographic structuring observed within the Asian clade, suggesting gene flow among the populations. However, sub-clades were found to form to among the local isolates, suggesting the existence of diversity among the isolates. Results from the SI test indicated that the R. microporus in the rubber plantations were clustered according to geographical regions based on a dendrogram generated from Unweighted Pair Group Method with Arithmetic Means (UPGMA) analysis. On the basis of ISSR data, the clustering of isolates revealed a pattern of genetic variation in correlation with the different geographical regions. The dendrogram from SI analysis is in congruent with the dendrogram generated based on ISSR data. These findings provide insights into the studies of genetic and details documentation on R. microporus associated with WRR disease of rubber in Malaysia.